1985
DOI: 10.1152/jappl.1985.58.1.187
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular reactions to cold exposures differ with age and gender

Abstract: This study was conducted since virtually no information was available concerning age- and gender-related differences in cardiovascular adjustments to cold exposure. Men and women between the ages of 20 and 30 and 51 and 72 yr, wearing swim suits, rested for 2 h in 28, 20, 15, and 10 degrees C ambient temperatures (Ta), with 40% relative humidity. Cardiac output (Qc) and stroke volumes (Qs) were higher in younger than older subjects regardless of Ta. Cardiac output was not influenced by gender, but all cold exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
45
1

Year Published

1990
1990
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(55 citation statements)
references
References 0 publications
7
45
1
Order By: Relevance
“…Interestingly, not only cooling the face but even the inhalation of cold air increases muscle sympathetic nervous activity and blood pressure (Heindl et al 2004). The whole body cooling in wakeful subjects also increases systolic and diastolic blood pressure (Korhonen 2006;Leppaluoto et al 2001), and decreases heart rate (Korhonen 2006;Wagner et al 1985). The results of our study may also be related to cold exposure itself and breathing cold air during sleep.…”
Section: Discussionsupporting
confidence: 53%
“…Interestingly, not only cooling the face but even the inhalation of cold air increases muscle sympathetic nervous activity and blood pressure (Heindl et al 2004). The whole body cooling in wakeful subjects also increases systolic and diastolic blood pressure (Korhonen 2006;Leppaluoto et al 2001), and decreases heart rate (Korhonen 2006;Wagner et al 1985). The results of our study may also be related to cold exposure itself and breathing cold air during sleep.…”
Section: Discussionsupporting
confidence: 53%
“…Although systolic blood pressure has been shown to increase with skin cooling (15,29,58,60), the concomitant decrease in heart rate minimizes the effects of cooling on RPP. Similarly, whole body exposure to 5°C air has been shown to increase systolic blood pressure, lower heart rate, and increase stroke volume in both supine (48) and seated volunteers (46,57), but these studies involved mild shivering, which makes a direct comparison with the present study challenging.…”
Section: Discussionmentioning
confidence: 84%
“…With these ®ndings taken into account, we assume that the applied thermoregulatory stimulation was similar in the two groups regardless of body fat content. Considering the physiological responses to a cold environment reported in previous research, 20,22,36 and the patterns of the autonomic nervous system found in the obese group (the reduction of HR, and the increase in the HI frequency component and the TOTAL power without any change in the VLO nor LO frequency components), it might be speculated Figure 4 Comparison of the delta change in very low (DVlow), low (DLow) and high (DHigh) frequency components from comfortable room temperature (25 C) to the cold environment (10 C) between the control and obese groups. Results are expressed as mean AE s.e.m.…”
Section: Discussionmentioning
confidence: 99%